2009
DOI: 10.1177/147470490900700107
|View full text |Cite
|
Sign up to set email alerts
|

Tearing: Breakthrough in Human Emotional Signaling

Abstract: Abstract:Tearing is not a benign secretory correlate of sadness or other emotional state, but a potent visual cue that adds meaning to human facial expression, the tear effect. Although tearing (lacrimation) provides ocular lubrication and is a response to irritation in many animals, emotional tearing may be unique to humans and does not develop until several months after birth. This study provides the first experimental demonstration that tears are a visual signal of sadness by contrasting the perceived sadne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
109
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 3 publications
18
109
1
Order By: Relevance
“…Based on earlier findings by Provine et al (2009), we expected to find a similar superior recognition of sadness when tears were present. We furthermore expected to find an increased perceived need for support among people with tearful faces.…”
Section: Introductionmentioning
confidence: 97%
“…Based on earlier findings by Provine et al (2009), we expected to find a similar superior recognition of sadness when tears were present. We furthermore expected to find an increased perceived need for support among people with tearful faces.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, recent empirical work suggests that emotional tears increase receiver perceptions of sadness (Balsters, Krahmer, Swerts, & Vingerhoets, 2012;Provine & Brocato, 2009) and sincerity (Zeifman & Brown, 2011). In a study comparing static images of individuals with and without tears, Provine, Krosnowski, and Brocoto (2009) found that individuals portrayed with tears were perceived as sadder in appearance.…”
Section: Introductionmentioning
confidence: 99%
“…We all feel we learn something about a person in tears, but the nature of this information has been poorly studied. For this reason, studies such as Provine, Krosnowski and Brocato (2009) (PKB), that isolate the effect of tears on spectators from that of sad or crying facial expressions, are important 1 . PKB describes an experiment in which observers were asked to identify emotions in sad or crying faces seen with and without (digitally removed) tears.…”
Section: Introductionmentioning
confidence: 99%